Ethnographic Study on the Meaning of Cost in the Sasak’s Tradition Wedding - Miranda, Johan; Sokarina, Ayudia (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study is to reveal the meaning of cost in the traditional Sasak wedding tradition in Lombok, West Nusa Tenggara. This research uses an interpretive paradigm with ethnographic methodology. The results showed that cost in the traditional Sasak wedding tradition has a complex and multidimensional meaning. This study provides important insights in the development of accounting science, where costs in traditional marriage traditions, which have communal characteristics, contain a more humanist meaning than the meaning of costs in the modern view which is attached to the individualist character.